Pengembangan Sistem Informasi Pengusulan, Penilaian Dan Penetapan Angka Kredit Guru (SIPULPENPAKGURU) - Wawan Kusdiawan (LPPM STMIK Rosma, 2017)
Teacher Performance Assessment is one component in determining the ratings of Credit Master obtained through nomination DUPAK (List of Proposed Establishment of Credit). It is a collection of files that match the rules, bound and delivered to the Secretariat of the assessment team lists the ratings of teacher performance through a number of credits submitted by individual teachers or educators who have become civil servants are useful as one of the requirements at the higher promotion and/or salary or welfare of teachers as functional as well as teacher performance assessment materials or educators such. The problem faced today is publishing mechanism DUPAK still manual, especially in the process of assessment by the Assessment Team PAK. Thus, in the assessment process in the official report sheet assessment is done in handwritten form in a way, made possible mistakes or errors at the time of entry into application PAK. Teacher understanding of the mechanism of determination of PAK is still low, and the limited number of personnel for data processing. These problem will eventually be detrimental to civil servants, especially teachers concerned.With the implementation of this applications especially teachers with considerable amounts expected to help because it can improve the accuracy and is able to speed up service. Through the implementation of this SIPULPEKGURU expected nomination process that was previously done manually with the innovations made in this SIPULPENPAKGURU application development, finaly can be made online so that more accurate data, teachers can also monitor the progress of his nomination.